Sex differences and risk factors in recurrent ischemic stroke - Chung, Ji Yeon; Lee, Bit Na; Kim, Young Seo; Shin, Byoung-Soo; Kang, Hyun Goo (Frontiers in Neurology, 2023)
Introduction Recurrent ischemic stroke (RIS) is associated with increased mortality and poor outcomes. Therefore, secondary prevention is critical for reducing the risk of recurrent stroke. Previous studies have found sex differences in risk factors in patients with first-ever stroke; however, the results have been inconsistent for recurrent stroke. Therefore, this study aimed to investigate whether there are significant sex differences in the clinical characteristics and risk factors for recurrent ischemic stroke. Methods We retrospectively studied 787 patients with recurrent ischemic stroke after first-ever stroke confirmation using magnetic resonance imaging (MRI) after visiting a regional tertiary hospital between 2014 and 2020. Demographic characteristics, laboratory findings, and risk factors were compared between the male and female patients. In addition, multivariate logistic regression was performed to identify the independent factors associated with stroke recurrence in male patients. Results Among the 787 patients, 466 (59.2%) were males. Males were younger than females (67.6 vs. 71.9 years). Females had higher rates of hypertension, diabetes mellitus, dyslipidemia, and overweight than those of males. However, the alcohol drinking and smoking rate were significantly higher in males than that in females. There were no statistically significant sex-based differences in the laboratory findings. Among males, hypertension, alcohol drinking, smoking and dyslipidemia was a significant risk factor for ischemic stroke recurrence. Conclusion Hypertension and dyslipidemia were significant risk factors of recurrent ischemic stroke in both genders. Smoking and alcohol drinking were significant risk factors associated with ischemic stroke recurrence in males. Therefore, smoking cessation and alcohol abstinence are recommended after the first stroke to prevent recurrent ischemic stroke especially for males. Diabetes was a significant risk factor of ischemic stroke recurrence in females. More extensive studies are needed to understand the causal relationship of each factors with ischemic stroke recurrence according to sex differences and specification of preventive management is needed.